The Amenity Value of Agricultural Landscape and Rural-Urban Land Allocation - Aliza Fleischer; Yacov Tsur (European Regional Science Association (ERSA), 2005)
In this paper we study agricultural-urban land allocation in light of the rising amenity value of agricultural landscape. A given land area is to be allocated between a number of agricultural activities (crops) and urban use. Each activity (crop) area generates private benefits (profit from agricultural produce) and amenity benefits (open space, aesthetic landscape, hiking trails). Land allocated for housing provides only private benefits. Land markets overlook the social (environmental) role of agricultural land and as a result lead to undersupply of farmland. In an empirical study of an Israeli case, we find the undersupply of farmland and the associated deadweight loss to be substantial. Investigating effects of population and income growth processes, we find that, contrary to market outcomes, the socially optimal allocation may call for more farmland preservation under either process.
Keywords: 330